Analisis Strategi Pemasaran Produk Gadai Emas Pada Bank Syariah Indonesia KC Lubuk Pakam - Pohan, Rahma Nur Azizah; Jannah, Nurul (Medan Resource Center, 2022)
Sharia pawning (Ar-Rahn) is a debt contract where goods have value as collateral so that the person concerned can take the debt. In this rahn contract system, the Lubuk Pakam community can obtain financing by going directly to a sharia bank with a fast, safe and practical process. This study aims to find out how the marketing strategy of gold pawn products at Islamic banks, and can see how the development of ema pawn products is carried out by marketing parties. The method used in this research is using a qualitative method using primary data from interviews with parties who have trusted sources regarding the gold pawn in order to obtain accurate data and information, and using secondary data obtained from literature, books, journals related to pawning gold as well as other sources related to this journal.